Investigation of Technology Management Process Implementation in SMEs in Klang Valley - Syazrie Adley, Nor Azman; Liu, Yao; Puteri Fadzline, Muhamad Tamyez (Universiti Malaysia Pahang, 2017)

(untitled)
SMEs uses various process and methods to manage its technology manangement process. This study demonstrate a survery of SMEs in Klang Valley that shows how companies identify, monitor and asses process and methods of its technology management process in the category of technology, economic, customer needs and competitors.